Large bias-induced piezoelectric response in the ferroelectric polymer P(VDF-TrFE) for MEMS resonators - Jonas Hafner (Materials Research Letters, 2021)
Piezoelectricity in ferroelectrics arises from electrostriction biased by their spontaneous polarisation, which can be enhanced through a bias-induced polarisation. Doing so, the piezoelectric response can be tuned and significantly enhanced. In this study, the ferroelectric polymer P(VDF-TrFE) was used to electro-mechanically excite a silicon microcantilever. Using this device, we demonstrate that a bias-induced polarisation improves the piezoelectric response of P(VDF-TrFE). To distinguish between the linear piezoelectric and quadratic electrostrictive effect, lock-in measurements were performed in order to separate the characteristic frequency response of both electro-mechanical phenomena. This work shows the potential for MEMS devices having controllable actuating and sensing properties.